Students" e-profiling / Nor Jaslina Nik Wil ...[et al.] - Nik Wil, Nor Jaslina; Tumiran, Siti Dalina; Che Hassan, Anita; Asat, Siti Haliza; Wan Hashim, Wan Murshida (Universiti Teknologi MARA Cawangan Kelantan, 2019)
Having a complete and adequate data profiling system about students is very vital as it can be used to obtain statistics or informative summaries on any matters concerning students. Currently, in UiTM Cawangan Kelantan (UiTMCK), the students’ data could be found in the data system which is only available at the Hal Ehwal Akademik Department but with limited access. There are two types of data keeping in UiTMCK namely paper printed version and soft copy. The data of paper printed version are ept in the students file gathered during registration and are quite comprehensive whereas the soft copy data is concerned students’ academic results only. Thus, to have a one stopcenter and fast-tracking of students’ data profiling, a system to collect information is created known as Students’ eProfiling (SeP). This system is meant for collecting data in order to get information about students’ background concerning non-academic matters. The system is unique in the sense that it can be accessed either by using QR code or a link for the students to fill up required particulars. The system is beneficial as it could help academic staff to identify the students in terms of income, health or any physical limitation that needs further attention. The information gathered through this system could be used in the process of zakat selection, food bank selection, time table preparation etc